Epistemological Beliefs, Information-Search Strategies and Criteria for the Validation of Web Information - Rubén Darío Martínez Vidal; Yolanda Haydeé Montero Mauro; María Eugenia Pedrosa Borrini (Universidad Autónoma de Baja California, 2010)
This work describes an exploratory study of 286 junior high school students in Mar del Plata, Argentina, regarding the themes: a) places and frequency of access to the Internet; b) strategies used by students in searching the Internet for relevant information; c) the way in which they validate and make sense of the data obtained; and d) students' epistemological beliefs. Results indicated that: a) participants were more willing to use ready-made search strategies and superficial approaches for the validation of information; b) different frequencies of Internet access revealed no impact on the search strategies; c) students showed an intermediate epistemological development; d) various interrelationships were found between epistemological beliefs, Internet-search strategies, and criteria for validating web information; and e) girls showed epistemological beliefs slightly more sophisticated than those of boys.